FRI0272 Pharmacodynamic effects of atacicept treatment in a cynomolgus monkey klh antigen challenge model. (12th June 2018) - Samy, E.; Bender, A.; Wu, Y.; Castagna, V.; Bertotti, E.; Boggio, R.; Paoletti, A.; Riva, S.; Schneider, P.; Haselmayer, P.; DeMartino, J.
Abstract : Background: Atacicept is an antagonist of the B cell regulatory factors BLyS (B lymphocyte stimulator) and APRIL (a proliferation inducing ligand). It is capable of binding to all known conformations of BLyS and APRIL and is thus expected to modulate the maturation, differentiation, and effector function of B cells. We aimed to define the relationship between atacicept drug exposure and pharmacodynamic (PD) effects in vivo . Here, we report results of our study examining the effects of atacicept on the immune response in a keyhole limpet hemocyanin (KLH) challenge model in cynomolgus monkeys. Methods: Cynomolgus monkeys (Macaca fascicularis) were injected with KLH on Day −33, and on Day 1 received the first dose of either atacicept (0.3, 3, or 30 mg/kg) or vehicle followed by a KLH challenge. Animals were dosed weekly (Day 1, 8, 15) and were subsequently monitored for 2 weeks before the study ended on Day 29. Clinical signs, total and free drug levels, peripheral blood B and T cell subpopulations, and total and KLH-specific immunoglobulin (Ig) levels were monitored. Additionally, gene expression in blood was analysed using the NanoString nCounter platform. Results: Atacicept was well-tolerated at all dose levels tested. All animals in the treatment arms had quantifiable levels of atacicept in serum throughout the study. Reduction of serum IgM and IgG was detected 7 days after treatment, with a continuous reduction in the mean serum IgM and IgG levels observed until Day 29 (table 1). In animals treated with 3 and 30 mg/kg atacicept, a significant decrease in serum anti-KLH IgG levels was observed versus vehicle-treated controls, beginning at Day 11 (table 2). A minor reduction in absolute CD3-CD20+, IgD +B cell numbers was seen in response to treatment, but no changes in T cell subsets were detected. Changes in gene expression following atacicept treatment were predominantly observed in B cell-related and Ig genes. Conclusions: This study showed that atacicept modulates B cell responses, IgM and IgG levels, and Ig isotype switching in a KLH-antigen-challenged cynomolgus monkey model, thus supporting its use in the treatment of antibody-mediated diseases. Additionally, gene expression PD markers identified in this study will be used in subsequent clinical trials as exploratory PD readouts. Disclosure of Interest: E. Samy Employee of: EMD Serono Research and Development Institute, Inc. (a business of Merck KGaA, Darmstadt, Germany), A. Bender Employee of: EMD Serono Research and Development Institute, Inc. (a business of Merck KGaA, Darmstadt, Germany), Y. Wu Employee of: EMD Serono Research and Development Institute, Inc. (a business of Merck KGaA, Darmstadt, Germany), V. Castagna Employee of: Istituto di Ricerche Biomediche Antoine Marxer RBM SpA, an affiliate of Merck KGaA, E. Bertotti Employee of: Istituto di Ricerche Biomediche Antoine Marxer RBM SpA, an affiliate of Merck KGaA, R. Boggio Employee of: Istituto di Ricerche Biomediche Antoine Marxer RBM SpA, an affiliate of Merck KGaA, A. Paoletti Employee of: Istituto di Ricerche Biomediche Antoine Marxer RBM SpA, an affiliate of Merck KGaA, S. Riva Employee of: Istituto di Ricerche Biomediche Antoine Marxer RBM SpA, an affiliate of Merck KGaA, P. Schneider Grant/research support from: EMD Serono Research and Development Institute, Inc. and Merck KGaA, P. Haselmayer Employee of: Merck KGaA, J. DeMartino Employee of: EMD Serono Research and Development Institute, Inc. (a business of Merck KGaA, Darmstadt, Germany)